Educación tecnológica: una nueva asignatura en todo el mundo - Gilbert, J. K. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1995)
This paper has three interlocking themes. The first relates to rationales for the inclusion of technology education in the school curriculum worldwide. The second deals with the issues that have to be addressed as that inclusion is either made or extended. The third is the relation between technology and the environment, which has implications for the problems addressed by technology education.